Ineffective changes for hard times. The 2017 reform of the Italian Senate’s Rule of Procedure and its effects - Andrea Pedrazzani; Francesco Zucchini (Italian Political Science, 2020)
In 2017, an extensive reform of the Rules of Procedure of the Italian Senate was enacted. The revision was soon welcomed as a step towards a more efficient and rapid upper house. In this article, we focus on one crucial aspect of the reform: the changes made to the rules governing the assignment of bills to parliamentary committees. In particular, we analyze the costs associated with the different assignment procedures and develop some theoretical expectations about the change brought about by the reform in terms of decision-making efficiency. These expectations are empirically evaluated against data on lawmaking in the Senate before and after the reform. A comparison is also carried out using data from the Chamber of Deputies. Preliminary results show that the new rules have not improved the efficiency and productivity of the Italian Senate so far.